EFEKTIVITAS MODEL PEMBELAJARAN LEARNING CYCLE 7E PADA SISWA KELAS VIII PADA MATERI GETARAN DAN GELOMBANG DI SMP NEGERI 3 JOMBANG TAHUN AJARAN 2018/2019 - zuhrotun nurani zahra; Nur Kuswanti; Noer Af'idah (Wacana Didaktika, 2019)
The objectives of this study were describing the effectiveness of the 7E Learning Cycle learning model on Vibration and Wave material in State Junior High School 3 Jombang (1) describe the activities of student using the Learning Cycle model 7E (2) describe the student learning outcomes after learning using the Learning Cycle learning model 7E (3) to descrThe objectives of this study were describing the effectiveness of the 7E Learning Cycle learning model on Vibration and Wave material in State Junior High School 3 Jombang (1) describe the activities of student using the Learning Cycle model 7E (2) describe the student learning outcomes after learning using the Learning Cycle learning model 7E (3) to describe students responses to the learning using the Learning Cycle 7E learning model. The type of research used was Pre-eksperimental Design and the design form is One-Shot Case Study. The sample used in this study was class VIII E students consisting of 29 students taken by purposive sampling technique, namely sampling techniques with certain considerations. The results of observations showed that students were active in learning using the 7E Learning Cycle model with an average of 74,36% with active category. Student learning outcomes had a classical completeness value of 68% so that student learning outcomes were not completed because it was less than 75%. The learning indicators obtained classical completeness values of 42,85% with incomplete categories. While the students positive response to learning using the 7E Leaning Cycle got to 100%. It could be cocluded that the 7E Learning Cycle learning model was less effective for Vibration and Wave material.ibe students responses to the learning using the Learning Cycle 7E learning model. The type of research used was Pre-eksperimental Design and the design form is One-Shot Case Study. The sample used in this study was class VIII E students consisting of 29 students taken by purposive sampling technique, namely sampling techniques with certain considerations. The results of observations showed that students were active in learning using the 7E Learning Cycle model with an average of 74,36% with active category. Student learning outcomes had a classical completeness value of 68% so that student learning outcomes were not completed because it was less than 75%. The learning indicators obtained classical completeness values of 42,85% with incomplete categories. While the students positive response to learning using the 7E Leaning Cycle got to 100%. It could be cocluded that the 7E Learning Cycle learning model was less effective for Vibration and Wave material.